Changes in the Perception of Ground Beef Quality as a Result of Primal Labeling - L. A. Egger; K. M. Harr; E. S. Beyer; K. J. Farmer; S. G. Davis; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to determine the effect of providing primal source information to consumers prior to consumption on palatability ratings of ground beef from the same source. Study Description:Ground beef chubs that were 80% lean and 20% fat (n = 15) were used for testing. Samples were served to consumers as 0.25 lb patties that were cooked internally to 160°F. Consumers were asked to evaluate and assess different palatability traits and evaluated samples identified as ground chuck, ground round, ground sirloin, and store ground along with a sample that offered no information. Bottom Line:Based on this research, the addition of primal source labeling improves consumer perception of the palatability traits of ground beef and the likelihood of consumer purchase.
Keywords: ground beef; palatability; consumer; primal source; labeling